2018
DOI: 10.1021/acs.energyfuels.8b03258
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study on Aggregating Behavior of Asphaltene and Resin in Emulsified Heavy Oil Droplets with Sodium Dodecyl Sulfate

Abstract: The aggregates of asphaltene and resin molecules play an important role in stabilizing heavy crude oil. Although many experiments are applied to investigate the complex aggregating structure of asphaltene and resin molecules in heavy crude oil, those microstructure and properties are still not clear at the molecular level. As another auxiliary tool, molecular dynamics (MD) simulation can be used to simulate the behavior of asphaltene and resin in the heavy oil droplet or emulsified oil droplet. The simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 48 publications
0
48
0
1
Order By: Relevance
“…In order to get as close as possible to the real situation, the oil model was designed based on Miranda’s works [ 48 , 49 ], which were used to explore the interface properties between crude oil and different fluids. Their model contained alkanes (72 hexane, 66 heptane, 78 octane, and 90 nonane molecules), cyclanes (48 cyclohexane and 78 cycloheptane molecules), and aromatics (30 benzene and 78 toluene molecules), and has been proven reliable by Song et al [ 50 ].…”
Section: Simulation Methodsmentioning
confidence: 99%
“…In order to get as close as possible to the real situation, the oil model was designed based on Miranda’s works [ 48 , 49 ], which were used to explore the interface properties between crude oil and different fluids. Their model contained alkanes (72 hexane, 66 heptane, 78 octane, and 90 nonane molecules), cyclanes (48 cyclohexane and 78 cycloheptane molecules), and aromatics (30 benzene and 78 toluene molecules), and has been proven reliable by Song et al [ 50 ].…”
Section: Simulation Methodsmentioning
confidence: 99%
“…They concluded that both temperature and asphaltene concentration could play a significant role in the behavior of asphaltene molecules at a water–toluene interface; this behavior can vary from a solute-like agent to surfactant-like molecules. Song et al 55 carried out MD simulation on a mixture of asphaltene and resin in the presence of an anionic surfactant, i.e., Sodium Dodecyl Sulfate. Based on their results, adding surfactants facilitate a viscosity reduction in heavy oils due to a weak interaction between resins and asphaltene molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their outcomes, changing the grooves' size and shape on the silica surface changed the amount of adsorbed heavy oil onto the silica surface. Also, the presence of water molecules could decrease the adsorption of heavy oil onto the silica surface 2018 Song et al 55 300 0.1 GROMOS 53a6 60 Sodium dodecyl sulfate Asphaltene and Resin De-emulsification of the asphaltene-water system was investigated through a molecular simulation study. According to their results, SDS could increase the hydrophilic area on the water-asphaltene surface and de-emulsify the oil droplet in the water phase 2018 Khalaf and Mansoori 63 300 0.1 Optimized potentials for liquid simulations: all atom (OPLS-AA) 64 , 65 Three different Asphaltene The onset of asphaltene aggregation in three synthetic oil samples, comprised of n-heptane and o-xylene, was evaluated using molecular simulation.…”
Section: Introductionmentioning
confidence: 99%
“…( 图 10 稠油油滴网状结构 [43] . (a) 沥青质胶质等形成的堆积 结构; (b) 沥青质胶质等构成的网状结构(网络版彩图) 图 11 不同SDS浓度体系中乳化油滴表面的亲疏水表面 积 [43] (网络版彩图)…”
unclassified
“…Figure 11 The hydrophobic and hydrophilic surface area of emulsified heavy oil with different SDS concentration [43] (color online).…”
mentioning
confidence: 99%